In vitro Susceptibility Testing of Essential Oils against Gram-positive and Gram-negative Clinical Isolates, including Carbapenem-resistant Enterobacteriaceae (CRE). (4th October 2017) - Patterson, Jan E; McElmeel, M.L; Wiederhold, Nathan P
Abstract: Background: In the era of antibiotic resistance, alternative anti-infectives must be explored. The National Action Plan for Combating Antibiotic-Resistant Bacteria calls for developing nontraditional therapeutics, including natural compounds such as essential oils (EOs) (Goal 4.4). A pilot study previously showed in vitro activity of EOs against CRE and warranted further study of their antibacterial activity. We studied cinnamon bark, clove, lavender, lemongrass, eucalyptus, oregano, rosemary, thyme, tea tree, manuka, and Thieves® blend (Young Living Essential Oils, Lehi UT) against an expanded panel of Gram-positive and Gram-negative isolates. Methods: 30 Gram-positive and 70 Gram-negative clinical isolates, including CRE, were tested using CLSI methods. Isolates were grown overnight on TSA; 0.5 McFarland suspensions in sterile water were swabbed over Mueller–Hinton agar using the Kirby–Bauer method. 20 μl of full-strength oils were pipetted onto blank paper disks in a sterile dish. Disks were placed aseptically onto the plates immediately after inoculating disks. Vancomycin was tested with Gram-positives and meropenem with Gram-negatives. Median zone diameters are shown. Results: EOs oregano, thyme, cinnamon bark, and lemongrass had the largest zones of inhibition against Gram-positive organisms and were larger than those of vancomycin for MRSA/MSSA. Cinnamon bark had the largest zone of inhibition against P. aeruginosa and was larger than that of meropenem. Oregano, thyme, cinnamon bark had the largest zones of inhibition against Enterobacteriaceae and were larger than those of meropenem against K. pneumoniae and E. cloacae . Conclusion: Essential oils showed significant in vitro activity against clinical isolates, including CRE. Further study of the clinical activity of essential oils is warranted. Disclosures: J. E. Patterson, Young Living Essential Oils: Independent Contractor, Salary